Study on the dynamic trends of moves into, out of, and within the city - Yoko Shimizu; Toru Nakayama; Hiroko Shimizu; Hiroko Morita (Japan Architectural Review, 2023)
Abstract The purpose of this study was to compare the trends of moving in and out of the city and moving within the city, and to identify more detailed demographic and social dynamics within the city. The study found that the trends of moving in and out of the city and moving within the city can be classified into six categories and that moving within the city plays a significant role in the social dynamics of the region. Even though there was an increase in terms of population, some trends in moves in showed an aging of the population and its impact on the local community. In the case of a decrease in population due to partial moves out by households, the former households remain in the area, so it was found that moving out does not necessarily mean a decrease in the number of households, and this does not lead to the occurrence of vacant houses. From these findings, it can be said that the trend of moving within the city should be taken into account when considering the future image of the community. We think that it is necessary to understand the events occurring in the region in more detail and reflect them in future land use and housing policy considerations in the planning process.